Serum metabolomic analysis in patients with Hashimoto’s thyroiditis - Jiang, Xiao; Zhao, Xinyu; Gu, Xiaotong; Luo, Tao; Li, Pengqian; Wan, Chuchu; Liu, Haixia (Frontiers in Endocrinology, 2022)
Abstract Background: Hashimoto's thyroiditis, an autoimmune thyroid disease, shows high morbidity worldwide, particularly in female. Patients with Hashimoto's thyroiditis have an increasing risk of hypothyroidism during the occurrence and progression of Hashimoto's thyroiditis. In recent years, metabolomics has been widely applied in autoimmune diseases, especially thyroid disorders. However, metabolites analysis in Hashimoto's thyroiditis is still absent. Methods: A total of 92 samples were collected, including 35 cases in the control group, 30 cases in the Hashimoto's thyroiditis with euthyroidism group, and 27 cases in the Hashimoto's thyroiditis with subclinical hypothyroidism group. SPSS 25.0 for statistical analysis and ROC curve, SIMCA 14.0, Metaboanalysis for multifactor analysis, and Origin 2021 for correlation analysis. Results: 21 metabolites were identified. 10 metabolites were obtained from control group versus HTE group, 8 serum metabolites were abnormal between control group and HTS group, 3 metabolites were derived from HTE group versus HTS. Kyoto Encyclopedia of Genes and Genomes Enrichment analysis showed that fatty acid degradation, Arginine, and proline metabolism have a significant impact on HTE, while lysine degradation, tyrosine metabolism play an important role HTS group, compared to control group. In the comparison between the HTE and HTS group, Valine, leucine, and isoleucine degradation and Valine, leucine, and isoleucine biosynthesis exists a key role. Correlation analysis shows clinical are not related to metabolites. ROC curve indicates SM, LPC, PC can efficiency in identification patients with HT in different clinical stage from healthy individuals. Conclusion: Serum metabolites were changed in HT. Phospholipids such as SM, LPC, PC influence the pathogenesis of Hashimoto's thyroiditis. Fatty acid degradation and lysine degradation pathways have an impact on different clinical stage of HT.